PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIFE TIPE NUMBERED HEAD TOGETHER DENGAN SNOWBALL THROWING PADA SUB MATERI STRUKTUR DAN FUNGSI SEL DI KELAS XI SMA - Nurul Afni Berutu; Erlintan Sinaga (Universitas Negeri Medan, 2017)
This study aimed to difference the learning outcomes of students who were taughtusing cooperative learning model of Numbered Head Together with Snowball Throwing on subStructur and Function of Cells material. The population were all students of class XI SMANegeri 11 Medan distributed over three classes with the number of 202 people while thesample taken two classes of class XI IPA4 and XI IPA6 are taken in random sampling. The class XIIPA4 taught using cooperative learning model of Numbered Head Together while XI IPA6 classestaught using cooperative learning model Snowball Throwing. This type of research is anexperimental research. Instruments used in the study was an objective test 30 questions out of50 questions that have been tested validity. Based on the test results of data analysisrequirements of both classes of samples otherwise normal and homogeneous distribution. Theresults showed that the learning outcomes are taught using cooperative learning model ofNumbered Head Together higher with an average of 76.5 compared to the learning outcomesof student learning is taught using cooperative learning model Snowball Throwing with an average of 66. The difference it also proved by testing the hypothesis by using t-test withsignificance level α = 0.05, where tcount > ttable (6.54 > 1.66) were significant in this study Haaccepted and H0 rejected. It can be concluded that there are significant differences betweenthe learning of students who are taught using cooperative learning model of Numbered HeadTogether the type cooperative learning model Snowball Throwing on sub Structur andFunction of Cells material.Keywords: Learning outcomes, Numbered Head Together, Throwing Snowball.